Complex-phase fluorescent ceramic, preparation method thereof and light-emitting device

By covering the SiO2 layer on the surface of the phosphor particles and adopting a specific sintering process, the problem of poor binding force of the phosphor grains and alumina particles in the complex phase fluorescent ceramics is solved, and high fluorescence with high density and good luminescence performance is obtained Powder content complex phase fluorescent ceramics are suitable for laser lighting and display technology needs.

CN119219409APending Publication Date: 2024-12-31YLX INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310749611.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

When the existing complex phase fluorescent ceramics increase the content of the phosphor grains, it is difficult to obtain high density and poor binding force of the phosphor particles with alumina particles, which affects the luminescence performance and subsequent processing packaging.

Method used

By covering the SiO2 layer on the surface of the phosphor particles, and using a two-step sintering method of discharge plasma sintering and thermal isostatic sintering, combined with appropriate sintering aids, the binding force between the phosphor grains and alumina grains is improved, and the preparation Complex phase fluorescent ceramics with high phosphor content.

Benefits of technology

The complex phase fluorescent ceramic with high phosphor content has high density and good luminous properties, while improving mechanical properties, which are suitable for subsequent processing and packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219409A_ABST
    Figure CN119219409A_ABST
Patent Text Reader

Abstract

The invention discloses a complex-phase fluorescent ceramic, a preparation method thereof and a light-emitting device. The mass fraction of fluorescent powder crystal grains in the complex-phase fluorescent ceramic provided by the invention is 70-90%; and the relative density of the multiphase fluorescent ceramic is 99.0%-99.9%. The multiphase fluorescent ceramic has high density under the condition of high fluorescent powder crystal grain content, and the problem of poor binding force between large-particle-size fluorescent powder crystal grains and small-particle-size aluminum oxide crystal grains is effectively solved, so that the multiphase fluorescent ceramic has good mechanical performance and coating performance while having better luminescence performance; and subsequent processing and packaging are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of solid-state lighting technology, and in particular to a complex phase fluorescent ceramic and a preparation method and a light-emitting device thereof. Background Art

[0002] Laser lighting display technology mainly uses blue laser to excite fluorescent materials to obtain fluorescence in other bands. With the continuous development of laser lighting and display technology, the requirements for the performance of fluorescent materials are also increasing. Fluorescent materials need to have higher light conversion efficiency, luminous brightness and thermal conductivity to carry higher power density blue lasers.

[0003] Therefore, fluorescent ceramic materials came into being. There are mainly two types of fluorescent ceramic materials: one is pure phase fluorescent ceramics, which include yttrium aluminum garnet phosphor, but the thermal conductivity and luminescence performance do not meet the application requirements; the other is complex phase fluorescent ceramics, in which alumina is added to the phosphor and sintered together. The presence of alumina improves the thermal conductivity and luminescence performance of the fluorescent ceramics.

[0004] However, in the existing composite fluorescent ceramics, if you want to obtain ceramics with relatively high density, the content of phosphor cannot be very high, generally below 50%. If the content of phosphor is increased to improve the luminous performance of the composite fluorescent ceramic, since the phosphor particles are large and the alumina particles are small, the internal particles of the prepared fluorescent ceramics are not well combined, and it is difficult to obtain fluorescent ceramics with good density, which will lead to problems in subsequent processing and packaging. Summary of the invention

[0005] The present application provides a complex phase fluorescent ceramic and a preparation method thereof, so as to obtain a complex phase fluorescent ceramic with a high phosphor content.

[0006] The present application first provides a complex fluorescent ceramic, which includes aluminum oxide grains and phosphor grains; wherein the aluminum oxide grains have a particle size of 1-5 μm, and the phosphor grains have a particle size of 10-30 μm; the mass fraction of the phosphor grains in the complex fluorescent ceramic is 70% to 90%; and the relative density of the complex fluorescent ceramic is 99.0% to 99.9%.

[0007] The composite fluorescent ceramic contains SiO2, and the SiO2 accounts for 0.05%-5% of the mass of the fluorescent powder particles.

[0008] Among the phosphor crystal particles, at least 30% of the phosphor crystal particles have a particle size of more than 15 μm.

[0009] Wherein, the relative density of the composite fluorescent ceramic is 99.5%-99.9%.

[0010] Wherein, the shape of the phosphor crystal particles is smooth pebble-like.

[0011] The present application also provides a method for preparing a composite fluorescent ceramic, comprising:

[0012] Prepare phosphor particles, wherein the particle size of the phosphor particles is 10-30 μm, and coat the surface of the phosphor particles with a SiO2 layer;

[0013] Prepare alumina particles and a sintering aid, wherein the particle size of the alumina particles is 0.05 μm-1 μm;

[0014] The phosphor particles coated with the SiO2 layer, the aluminum oxide particles and the sintering aid particles are mixed in proportion to obtain a raw material powder, wherein the weight ratio of the phosphor particles to the aluminum oxide particles is 7-9:1-3;

[0015] Molding the raw material powder to obtain a green body;

[0016] The green body is subjected to a first sintering step, wherein the first sintering step satisfies at least one of a sintering temperature of 1400° C. to 1600° C., a sintering time of 0.5 h to 3 h, and a sintering pressure of 30 to 100 MPa;

[0017] The green body sintered in the first step is subjected to a second step of sintering, wherein the second step of sintering satisfies at least one of a sintering temperature of 1400° C. to 1700° C., a sintering time of 10 min to 100 min, and a sintering pressure of 100 to 200 MPa;

[0018] The green body sintered in the second step is annealed to obtain the composite fluorescent ceramic.

[0019] Wherein, the step of coating the surface of the phosphor particles with a SiO2 layer comprises:

[0020] The phosphor particles, solvent and alkoxysilane are mixed, and the alkoxysilane is hydrolyzed to coat the surface of the phosphor particles with a SiO2 layer, wherein the SiO2 layer accounts for 0.05% to 5% of the mass of the phosphor particles.

[0021] Wherein, the first step of sintering is spark plasma sintering; and the second step of sintering is hot isostatic pressing sintering.

[0022] Wherein, the sintering aids are magnesium oxide and yttrium oxide, and the sintering aids account for 0.1% to 5% of the mass of the aluminum oxide particles.

[0023] The present application further provides a light-emitting device, comprising an excitation light source and the complex phase fluorescent ceramic as described above.

[0024] Beneficial effects of the present application: Different from the prior art, the complex phase fluorescent ceramics provided by the present application have higher density with a high content of phosphor grains, and effectively solve the problem of poor bonding between large-size phosphor grains and small-size alumina grains, so that the complex phase fluorescent ceramics have better luminous performance while having good mechanical properties and coating properties, which is beneficial to subsequent processing and packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic structural diagram of the first embodiment of the composite fluorescent ceramic of the present application;

[0026] Figure 2 It is a schematic diagram of the process of the first embodiment of the preparation method provided by the present application;

[0027] Figure 3 is a schematic structural diagram of a comparative embodiment of a fluorescent ceramic;

[0028] Reference numerals: complex phase fluorescent ceramic 1 ; phosphor crystal grains 11 ; aluminum oxide crystal grains 12 ; complex phase fluorescent ceramic 2 ; phosphor crystal grains 21 ; aluminum oxide crystal grains 22 ; holes 23 . DETAILED DESCRIPTION

[0029] The primary purpose of the present application is to increase the content of phosphor crystals in a composite fluorescent ceramic formed by combining phosphor crystals and aluminum oxide crystals, so as to improve the luminescent performance of the composite fluorescent ceramic.

[0030] Based on the above purpose, the technical scheme in the embodiment of the present application will be clearly and completely described below in conjunction with the drawings of the embodiment of the present application. It will be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. In the absence of conflict, the following embodiments and the technical features therein may be combined with each other. It should also be noted that, for ease of description, only some but not all structures related to the present application are shown in the drawings. Based on the embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of this application.

[0031] In order to improve the thermal conductivity and luminescence performance of fluorescent ceramics, in the prior art, alumina powder is added to phosphor particles for sintering. However, since the particle size of the phosphor particles is relatively large and the particle size of the alumina powder is relatively small, if the phosphor particle content is relatively high, the bonding effect between the phosphor particles and the alumina powder will be poor during sintering. Therefore, the phosphor grain content in the fluorescent ceramics prepared at present is not high.

[0032] Since the phosphor crystals provide luminescent centers in the fluorescent ceramic, when the fluorescent ceramic receives excitation light, the phosphor crystals in the fluorescent ceramic can absorb the excitation light and generate light beams of other bands. The more phosphor crystals in the fluorescent ceramic, the more light beams are generated, which can effectively improve the luminescent performance of the fluorescent ceramic. For the current laser lighting and display technology fields, a complex phase fluorescent ceramic with a higher phosphor content is needed. Therefore, the present application proposes a complex phase fluorescent ceramic with a high phosphor content.

[0033] Please combine Figure 1 As shown, Figure 1 1 is a schematic diagram of the structure of the first embodiment of the composite fluorescent ceramic of the present application. The composite fluorescent ceramic 1 of the present application comprises fluorescent powder grains 11 and aluminum oxide grains 12.

[0034] The phosphor crystal particles 11 can absorb the excitation light and emit fluorescence in other bands for use by users or fluorescent devices. Among them, the phosphor crystal particles 11 can be formed by YAG:Ce (cerium-doped yttrium aluminum garnet) yellow phosphor or LuAG:Ce (cerium-doped lutetium aluminum garnet) green phosphor, red phosphor and other phosphor particles. For example, under the stimulation of blue excitation light, the YAG:Ce yellow phosphor will emit yellow visible light and emit it to the outside of the composite fluorescent ceramic 1 through the alumina crystal particles 12. In one embodiment, the phosphor crystal particles 11 can be Re:YAG (yttrium aluminum garnet, Y3Al5O 12 ) phosphor particles, wherein Re is selected from one of cerium (Ce), lutetium (Lu), europium (Eu), neodymium (Nd), terbium (Tb), ytterbium (Yb) and praseodymium (Pr).

[0035] In this embodiment, in the sintered fluorescent ceramic, the phosphor crystal grains 11 are evenly distributed in the alumina crystal grains 12. When the phosphor crystal grains 11 absorb the excitation light in the complex fluorescent ceramic 1, they generate and emit a light beam, providing a luminescent center for the complex fluorescent ceramic 1. The mass of the phosphor crystal grains 11 in the complex fluorescent ceramic 1 accounts for 70% to 90%, and the mass fraction of the phosphor crystal grains 11 can be 71%, 72%, 73%, 75%, 76%, 78%, 80%, 81%, 82%, 83%, 85%, 86%, 88%, 89%, 89.5%, etc. The obtained complex fluorescent ceramic 1 has a high phosphor crystal grain content, which can provide more luminescent centers for the complex fluorescent ceramic 1, generate more light beams when receiving the excitation light, and improve the luminescent performance of the complex fluorescent ceramic 1.

[0036] Moreover, in the composite fluorescent ceramic 1 of one embodiment, the particle size of the alumina grains 12 is 1-5 μm, preferably 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm. During the sintering process of the fluorescent ceramic, the alumina particles will undergo a melting-binding process, thereby forming alumina grains 12 of different particle sizes, which are combined around the phosphor grains 11, thereby improving the bonding force between the alumina grains 12 and the phosphor grains 11; at the same time, the alumina grains 12 of different particle sizes help to fill different gaps in the fluorescent ceramic, so that the composite fluorescent ceramic 1 of this embodiment has a high density.

[0037] The relative density of the composite fluorescent ceramic 1 obtained in this embodiment is 99.0%-99.9%, wherein the relative density can be obtained by the ratio of the apparent density to the true density, the apparent density can be determined by the ratio of the mass of the composite fluorescent ceramic 1 to the volume obtained by the Archimedean drainage method, and the true density can be the density obtained by theoretical calculation. Further, the relative density of the composite fluorescent ceramic 1 can be 99.0%, 99.1%, 99.3%, 99.5%, 99.6%, 99.8%, 99.9%, etc. The present application achieves high density with a high content of phosphor crystal particles 11.

[0038] Optionally, the composite fluorescent ceramic 1 contains SiO2 (silicon dioxide), and SiO2 may account for 0.05%-5% of the mass of the phosphor grains 11, and may further account for 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, etc.

[0039] In one embodiment of the present application, SiO2 can be covered on the surface of the phosphor particles before the phosphor particles are sintered to form a SiO2 layer; in another embodiment, SiO2 can also be directly added to the mixture of phosphor particles and alumina particles before the fluorescent ceramic is sintered. During the sintering process, SiO2 will change from solid to liquid and be free around the phosphor grains 11, promoting the combination of alumina particles to form alumina grains 12, and also promoting the combination of alumina grains 12 and phosphor grains 11, and improving the bonding force between alumina grains 12 and phosphor grains 11. Since SiO2 helps sintering and enhances the bonding force between phosphor grains 11 and alumina grains 12 during the sintering process, the mass of SiO2 should not be too small. However, if there is too much SiO2, too much liquid phase may be formed during the sintering process, which is not conducive to improving the bonding force between phosphor grains 11 and alumina grains 12, so the mass of SiO2 should not be too large. When SiO 2 accounts for 0.05%-5% of the mass of the phosphor crystal grains 11 , it can help sintering and enhance the bonding force between the phosphor crystal grains 11 and the aluminum oxide crystal grains 12 .

[0040] In one embodiment, the particle size of the phosphor particles 11 is 10-30 μm, preferably 11 μm, 12 μm, 15 μm, 16 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22.5 μm, 25 μm, 27.5 μm, 28 μm, or 29 μm.

[0041] Further optionally, at least 30% of the total number of phosphor crystal particles 11 in the phosphor crystal particles 11 have a particle size of more than 15 μm.

[0042] The phosphor crystals 11 with larger particle sizes are used in the present application because: in the complex fluorescent ceramic 1, the phosphor crystals 11 will emit light beams of other bands after receiving excitation light, and the intensity of the light beams emitted by the phosphor crystals 11 is related to the particle size of the phosphor crystals 11. The smaller the particle size of the phosphor crystals 11, the lower the temperature at which the surface enters the liquid phase during the high-temperature sintering of the fluorescent ceramic, that is, the smooth outer contour of the surface is more easily destroyed, resulting in a greater decrease in the luminous intensity of the fluorescent ceramic after sintering. Therefore, it is necessary to select phosphor particles with larger particle sizes as raw materials to obtain phosphor crystals 11 with larger particle sizes. However, the larger the particle size, the better. The larger the particle size of the phosphor particles, the more difficult it is to sinter, and the more difficult it is to obtain a complex fluorescent ceramic 1 with high density.

[0043] Furthermore, in this embodiment, at least 30% of the phosphor grains 11 have a particle size of more than 15 μm, ensuring that the outer contour of enough phosphor grains 11 is not destroyed during the sintering process, providing a luminescent center for the sintered complex fluorescent ceramic 1, so that the complex fluorescent ceramic 1 has good luminescent properties.

[0044] It should be noted that the particle size of the phosphor crystal grains 11 and the particle size of the alumina crystal grains 12 in the composite fluorescent ceramic 1 of the present application can be determined by Figure 1 The structural diagram shown is respectively Figure 1 The diameters of the maximum circumscribed circles of the outlines of the phosphor crystal grains 11 and the aluminum oxide crystal grains 12 shown in the figure are measured as the particle sizes of the phosphor crystal grains 11 and the aluminum oxide crystal grains 12 , respectively.

[0045] Alternatively, if Figure 1As shown, in the embodiment of the present application, the shape of the phosphor grains 11 in the composite fluorescent ceramic 1 is smooth and pebble-like, so that the phosphor grains 11 provide a luminescent center in the composite fluorescent ceramic 1, maintain the best luminescent form, and improve the luminescent performance of the composite fluorescent ceramic 1. The higher the mass fraction of the phosphor grains 11 and the larger the particle size, the more difficult it is to sinter into a ceramic with high density. If the sintering driving force is increased by increasing the sintering temperature, it is easy to cause the edges of the phosphor grains 11 in the composite fluorescent ceramic 1 to dissolve, and the phosphor grains 11 are severely deformed to lose the best luminescent form, resulting in a sharp drop in the luminescent performance of the composite fluorescent ceramic 1. The design of the present application is realized by using high mass fraction and large particle size phosphor grains 11 to sinter to form a high-density composite fluorescent ceramic 1, so that the composite fluorescent ceramic 1 has good luminescent performance at the same time.

[0046] In summary, the mass of the phosphor grains 11 in the composite fluorescent ceramic 1 proposed in the present application reaches more than 70% of the mass of the composite fluorescent ceramic 1, which can provide a large number of luminescent centers for the composite fluorescent ceramic 1, and effectively improve the luminescent performance of the composite fluorescent ceramic 1. In addition, the bonding force between the phosphor grains 11 and the alumina grains 12 is improved, so that the density of the composite fluorescent ceramic 1 is ensured while the content of the phosphor grains 11 is increased.

[0047] In order to obtain the above-mentioned complex phase fluorescent ceramic 1, the present application also provides a method for preparing the complex phase fluorescent ceramic 1, such as Figure 2 As shown, Figure 2 It is a schematic flow chart of the first embodiment of the preparation method provided by the present application. It includes the following steps:

[0048] S11: preparing phosphor particles, and coating the surface of the phosphor particles with a silicon dioxide layer.

[0049] The particle size of the phosphor particles is 10-30 μm (the particle size of the phosphor particles and alumina particles as raw materials can be considered as the median particle size D50), preferably 12 μm, 15 μm, 17 μm, 20 μm and 25 μm. The SiO2 layer is coated on the surface of the phosphor particles, and the phosphor particles, solvent and alkoxysilane can be mixed. The solvent can include hydrochloric acid solution, ammonia solution, etc. The alkoxysilane will be hydrolyzed under the catalysis of the solvent to generate SiO2, which is attached to the surface of the phosphor particles, thereby forming a SiO2 layer coated on the surface of the phosphor particles.

[0050] In the embodiment of the present application, the SiO2 layer is 0.05% to 5% of the mass of the phosphor particles, preferably 0.1-1%. Since the SiO2 layer changes from a solid phase to a liquid phase during the sintering process, it helps sintering and enhances the bonding force between the phosphor particles and the aluminum oxide grains 12. Therefore, the mass of the SiO2 layer should not be too small. On the other hand, if the thickness of the coated SiO2 layer is too thick, too much liquid phase may be formed during the sintering process, which is not conducive to improving the bonding force between the phosphor particles and the aluminum oxide grains 12. Therefore, the thickness of the SiO2 layer should not be too large. In this embodiment, the mass of the SiO2 layer is 0.05-5% of the mass of the phosphor particles, which can effectively improve the bonding force between the phosphor particles and the aluminum oxide grains 12.

[0051] S12: preparing alumina particles and sintering aids.

[0052] In the embodiment of the present application, alumina particles with a particle size of 0.05 μm-1 μm and sintering aids are also prepared. Selecting small-sized alumina particles as raw materials and using them in combination with relatively large-sized phosphor particles can increase the filling density, which is beneficial to improving the density. At the same time, small-sized alumina particles can reduce the sintering temperature.

[0053] The type of sintering aid is not particularly limited in the present application, for example, it can be one or more of SiO2, MgO, CaO, Y2O3, La2O3, etc. In one embodiment of the present application, MgO and Y2O3 can be used as sintering aids, and specific raw materials such as magnesium nitrate and yttrium nitrate can be used to reduce the sintering temperature of the fluorescent ceramic during the sintering process to avoid the high temperature causing the smooth outer contour of the phosphor grains 11 formed by the phosphor particles to be destroyed. Of course, other types of raw materials can also be used, and are not particularly limited to magnesium nitrate and yttrium nitrate. In addition, the mass ratio of MgO to Y2O3 can be 0.2 to 5. At the same time, the sintering aid will become a liquid phase during the sintering process, promote the combination of alumina particles to form alumina grains 12, and at the same time make the alumina grains 12 better free around the phosphor grains 11, thereby improving the bonding force between the alumina grains 12 and the phosphor grains 11. In addition, the sintering aid product is gathered at the grain boundary of the phosphor crystal grains 11 after sintering, and can serve as a scattering phase of the multiphase fluorescent ceramic 1, playing a role in hindering the lateral propagation of light and reducing the diffusion of light.

[0054] The mass of the sintering aid is 0.1% to 5% of the mass of the alumina particles.

[0055] It is worth noting that the quality of the sintering aid is not the more the better. When too much sintering aid is added during sintering, the sintering aid may form too much liquid phase during the sintering process, which is not conducive to improving the bonding force between the phosphor grains 11 and the alumina grains 12, and will reduce the mechanical strength of the fluorescent ceramic. Therefore, in this embodiment, the mass of the sintering aid accounts for 0.1% to 5% of the mass of the alumina particles.

[0056] S13: mixing the phosphor particles coated with the silicon dioxide layer, the aluminum oxide particles and the sintering aid according to a certain proportion to obtain a raw material powder.

[0057] In one embodiment, the alumina particles and the sintering aid may be mixed in advance, and then mixed with the phosphor particles coated with the SiO2 layer obtained in step S11; in another embodiment, the phosphor particles coated with the SiO2 layer obtained in step S11 may be fully mixed with the alumina particles and the sintering aid. Further, the phosphor particles coated with the SiO2 layer, the alumina particles and the sintering aid may be fully mixed by dry ball milling, and then crushed and sieved to obtain a raw material powder.

[0058] The mixing ratio of the phosphor particles and the alumina particles can be varied, and the content of the phosphor crystals 11 in the composite fluorescent ceramic 1 provided by the present application reaches 70%-90%. In this embodiment, the weight ratio of the phosphor particles to the alumina particles can be 7-9:1-3.

[0059] S14: molding the raw material powder to obtain a green body, and performing a first step sintering and a second step sintering on the green body.

[0060] In one embodiment, the raw material powder obtained in step S13 can be filled into a graphite mold and pre-pressed to obtain a green body, and the green body can be subjected to a first sintering step and a second sintering step.

[0061] The first step of sintering can be spark plasma sintering, and the graphite mold containing the green body is placed in a spark plasma sintering furnace for spark plasma sintering. This process can be carried out in a vacuum or argon environment, and at least one of the sintering temperature is 1400-1600°C, the sintering pressure is 30-100MPa, and the sintering time is 0.5-3h.

[0062] The second step of sintering can be hot isostatic pressing sintering, and the green body after the first step of sintering is placed in a hot isostatic pressing furnace for hot isostatic pressing sintering. This process can be carried out in a nitrogen or argon environment, and at least one of the sintering temperature is 1400-1700°C, the sintering pressure is 100-200MPa, and the sintering time is 10-100min.

[0063] It is understandable that the SiO2 layer coated on the surface of the phosphor particles may form a solid solution with the alumina particles, sintering aids, etc. during the sintering process to help sintering; and after the sintering is completed, the silicon element in the final fluorescent ceramic is generally not present in the form of SiO2 in the fluorescent ceramic, but in the form of an intermediate solid solution. Therefore, in the embodiments of the present application, the calculation of the silicon oxide content in the fluorescent ceramic is still calculated in the form of SiO2.

[0064] During the sintering process of step S14, the SiO2 layer coating the phosphor particles can activate the grain boundaries of the phosphor grains 11. At the same time, sufficient liquid phase will be formed during the sintering process, so that the aluminum oxide particles can have better fluidity in the gaps between multiple phosphor grains 11. Under high pressure conditions, the pores inside the fluorescent ceramic are gradually filled, so that the phosphor grains 11 and the aluminum oxide grains 12 are more closely bonded to each other, effectively improving the density of the composite fluorescent ceramic 1.

[0065] The traditional preparation method is mainly sintering in atmospheric pressure or vacuum sintering. The driving force for densification of this method mainly comes from the crystallization-growth process of alumina particles in fluorescent ceramics and the liquid phase flow of sintering aids. When the content of large-size phosphor particles is high and the content of alumina grains is low, the sintering power is not enough to densify the fluorescent ceramics with this structure, that is, the material exchange and recrystallization process of alumina grains cannot promote the displacement and mutual combination of phosphor particles. If the sintering temperature is further increased (such as to 1800℃) to increase the sintering driving force, not only will it still fail to be sintered, but it will also easily cause serious deformation of the phosphor particles in the fluorescent ceramics (destroying the smooth surface), causing the luminescence performance of the phosphor particles to drop sharply.

[0066] In the process of sintering fluorescent ceramics with high-content and large-particle phosphor grains, the present application introduces a sufficiently large external pressure to promote the mutual bonding of large-particle phosphor grains and small-particle aluminum oxide grains (the large and small particle sizes here are relative to the particle sizes of phosphor grains and aluminum oxide grains, not the absolute large and small particle sizes) by coating the surface of the phosphor particles with a SiO2 layer and using a two-step sintering method of spark plasma sintering and hot isostatic pressing sintering during the sintering of fluorescent ceramics with high content and large-particle phosphor grains, which can effectively improve the bonding force between the phosphor grains 11 and the aluminum oxide grains 12. In addition, by coating the surface of the phosphor particles with a SiO2 layer and adding a sintering aid to reduce the temperature inside the fluorescent ceramics during the sintering process, the sintering temperature is lowered, and sintering densification is achieved at a lower sintering temperature, and the phosphor grains can maintain their original state well, and the luminous performance is not greatly affected, and finally a high-density and high-light-efficiency fluorescent ceramic is obtained.

[0067] In the present application, a SiO2 layer is coated on the surface of the phosphor particles before sintering, and a sintering aid is added to reduce the overall temperature of the fluorescent ceramic during the sintering process, thereby protecting the smooth pebble-like surface of the phosphor grains 11, thereby achieving a high density of the fluorescent ceramic with a high phosphor grain 11 content while ensuring the luminescent performance of the fluorescent ceramic.

[0068] S15: annealing the green body after the second step sintering.

[0069] In one embodiment of the present application, the second sintered green body obtained in step S14 can be annealed for 1-20 hours in air or a reducing gas (such as hydrogen, carbon monoxide, methane, etc.) at a temperature of 1100-1400°C to remove carbon ions and other impurity ions that have infiltrated into the fluorescent ceramic during the sintering process, thereby improving the luminous efficiency of the fluorescent ceramic.

[0070] The present application also provides a light-emitting device (not shown), comprising an excitation light source and a complex fluorescent ceramic 1. The complex fluorescent ceramic 1 can be arranged around the excitation light source, and when receiving the excitation light generated by the excitation light source, the phosphor crystals 11 in the complex fluorescent ceramic 1 absorb the excitation light and generate multi-angle fluorescence with different wavelengths from the excitation light for use by users or fluorescent devices.

[0071] For the composite fluorescent ceramics 1 with different contents of phosphor crystals 11, the preparation methods of the present application are different. For example, the proportion of phosphor particles and alumina particles in the raw material powder will be different, the quality of the SiO2 layer covering the phosphor particles will be different, the content of magnesium nitrate and yttrium nitrate in the sintering aid will be different, the sintering temperature, sintering time and sintering pressure required for spark plasma sintering and hot isostatic pressing will be different, and the temperature and time of annealing treatment will also be different. Figure 2 The preparation method of the composite fluorescent ceramic 1 provided in the present application is described.

[0072] Example 1

[0073] The preparation method of the composite fluorescent ceramic comprises the following steps:

[0074] Prepare YAG yellow phosphor particles with a particle size of 10 μm, mix the phosphor particles with deionized water, and stir them in a stirrer to keep the phosphor particles suspended and flowing. Add a 2% mass fraction of tetraethyl orthosilicate solution to the stirrer, and then slowly drip a hydrochloric acid solution. The hydrochloric acid solution promotes the hydrolysis of the tetraethyl orthosilicate solution. After the tetraethyl orthosilicate is hydrolyzed, a layer of SiO2 will be covered on the surface of the phosphor particles. Then, the phosphor particles coated with the SiO2 layer are centrifuged and dried to obtain phosphor particles covered with the SiO2 layer.

[0075] The above operation was repeated 4 times on the phosphor particles to obtain phosphor particles coated with 4 SiO2 layers.

[0076] Prepare alumina particles with a particle size of 0.05 μm and sintering aids (magnesium oxide and yttrium oxide), mix the phosphor particles coated with SiO2 layer, alumina particles, sintering aids and anhydrous ethanol, and ball mill for 2 hours. Dry the mixed raw materials at 80°C for 10 hours, then crush and sieve to obtain raw material powder. Among them, the mass of magnesium oxide in the sintering aid is 0.3% of the mass of alumina particles, the mass of yttrium oxide is 0.5% of the mass of alumina particles, and the mass ratio between phosphor particles and alumina particles is 7:3.

[0077] The raw material powder is heat treated at 600° C. for 2 hours, the heat treated raw material powder is ground and sieved, and the raw material powder is placed in a graphite mold and pre-pressed to obtain a green body.

[0078] The obtained green body is placed in a spark plasma sintering furnace, and the first step of sintering is carried out in a vacuum environment at a sintering temperature of 1400° C., a sintering pressure of 100 MPa, and a sintering time of 3 h.

[0079] The green body sintered in the first step was placed in a hot isostatic pressing furnace, and the second step sintering was carried out in a nitrogen environment at a sintering temperature of 1400° C., a sintering pressure of 100 MPa, and a sintering time of 100 min.

[0080] The green body sintered in the second step is annealed at 1100° C. for 20 hours in a reducing gas environment to remove carbon ions that have penetrated into the fluorescent ceramic during the sintering process.

[0081] The fluorescent ceramics can be further cut, ground and polished to obtain complex-phase fluorescent ceramics with high fluorescent powder content.

[0082] Example 2

[0083] The preparation method of the composite fluorescent ceramic comprises the following steps:

[0084] Prepare YAG yellow phosphor particles with a particle size of 20 μm, mix the phosphor particles with deionized water, and stir them in a stirrer to keep the phosphor particles suspended and flowing. Add a 2% mass fraction of tetraethyl orthosilicate solution to the stirrer, and then slowly drip a hydrochloric acid solution. The hydrochloric acid solution promotes the hydrolysis of the tetraethyl orthosilicate solution. After the tetraethyl orthosilicate is hydrolyzed, a layer of SiO2 will be covered on the surface of the phosphor particles. Then, the phosphor particles coated with the SiO2 layer are centrifuged and dried to obtain phosphor particles covered with the SiO2 layer.

[0085] The above operation was repeated for 6 times on the phosphor particles to obtain phosphor particles coated with 6 SiO2 layers.

[0086] Prepare alumina particles with a particle size of 0.08 μm and sintering aids (magnesium oxide and yttrium oxide), mix the phosphor particles coated with SiO2 layer, alumina particles, sintering aids and anhydrous ethanol, and ball mill for 2 hours. Dry the mixed raw materials at 80°C for 10 hours, then crush and sieve to obtain raw material powder. Among them, the mass of magnesium oxide in the sintering aid is 0.6% of the mass of alumina particles, the mass of yttrium oxide is 0.8% of the mass of alumina particles, and the mass ratio between phosphor particles and alumina particles is 8:2.

[0087] The raw material powder is heat treated at 600° C. for 2 hours, the heat treated raw material powder is ground and sieved, and the raw material powder is placed in a graphite mold and pre-pressed to obtain a green body.

[0088] The obtained green body is placed in a spark plasma sintering furnace, and the first step of sintering is carried out in a vacuum environment at a sintering temperature of 1500° C., a sintering pressure of 80 MPa, and a sintering time of 1 h.

[0089] The green body sintered in the first step was placed in a hot isostatic pressing furnace, and the second step sintering was carried out in a nitrogen environment at a sintering temperature of 1550° C., a sintering pressure of 175 MPa, and a sintering time of 50 min.

[0090] The green body sintered in the second step is annealed at 1100° C. for 20 hours in a reducing gas environment to remove carbon ions that have penetrated into the fluorescent ceramic during the sintering process.

[0091] The fluorescent ceramics can be further cut, ground and polished to obtain complex-phase fluorescent ceramics with high fluorescent powder content.

[0092] Example 3

[0093] The preparation method of the composite fluorescent ceramic comprises the following steps:

[0094] Prepare YAG yellow phosphor particles with a particle size of 30 μm, mix the phosphor particles with deionized water, and stir them in a stirrer to keep the phosphor particles suspended and flowing. Add a 1% mass fraction of tetraethyl orthosilicate solution to the stirrer, and then slowly drip a hydrochloric acid solution. The hydrochloric acid solution promotes the hydrolysis of the tetraethyl orthosilicate solution. After the tetraethyl orthosilicate is hydrolyzed, a layer of SiO2 will be covered on the surface of the phosphor particles. Then, the phosphor particles coated with the SiO2 layer are centrifuged and dried to obtain phosphor particles covered with a layer.

[0095] The above operation was repeated 8 times on the phosphor particles to obtain phosphor particles coated with 8 layers of SiO2.

[0096] Prepare alumina particles with a particle size of 1 μm and sintering aids (magnesium oxide and yttrium oxide), mix the phosphor particles coated with SiO2 layer, alumina particles, sintering aids and anhydrous ethanol, and ball mill for 1 hour. Dry the mixed raw materials at 60°C for 20 hours, then crush and sieve to obtain raw material powder. Among them, the mass of magnesium oxide in the sintering aid is 0.8% of the mass of alumina particles, the mass of yttrium oxide is 1% of the mass of alumina particles, and the mass ratio between phosphor particles and alumina particles is 9:1.

[0097] The raw material powder is heat treated at 600° C. for 2 hours, the heat treated raw material powder is ground and sieved, and the raw material powder is placed in a graphite mold and pre-pressed to obtain a green body.

[0098] The obtained green body is placed in a spark plasma sintering furnace for the first step of sintering in a vacuum environment with a sintering temperature of 1600° C., a sintering pressure of 30 MPa and a sintering time of 0.5 h.

[0099] The green body sintered in the first step was placed in a hot isostatic pressing furnace for the second step of sintering in a nitrogen environment at a sintering temperature of 1700° C., a sintering pressure of 200 MPa, and a sintering time of 10 min.

[0100] The green body sintered in the second step is annealed at 1400° C. for 5 hours in a reducing gas environment to remove carbon ions that have infiltrated into the fluorescent ceramic during the sintering process.

[0101] The fluorescent ceramics can be further cut, ground and polished to obtain complex-phase fluorescent ceramics with high fluorescent powder content.

[0102] Comparative Example

[0103] The preparation method of the composite fluorescent ceramic comprises the following steps:

[0104] Prepare YAG yellow phosphor particles with a particle size of 10 μm and alumina particles with a particle size of 0.05 μm, mix the phosphor particles, alumina particles and anhydrous ethanol, and ball mill for 2 hours. Dry the mixed raw materials at 80°C for 10 hours, then crush and sieve to obtain raw material powder. The mass ratio between the phosphor particles and the alumina particles is 7:3.

[0105] The raw material powder is heat treated at 600° C. for 2 hours, the heat treated raw material powder is ground and sieved, and the raw material powder is placed in a graphite mold and pre-pressed to obtain a green body.

[0106] The green body was placed in a hot isostatic pressing furnace and sintered in a nitrogen environment at a sintering temperature of 1800°C, a sintering pressure of 100 MPa, and a sintering time of 100 min.

[0107] The sintered green body was annealed at 1100° C. for 20 hours in a reducing gas environment to remove carbon ions that had infiltrated the fluorescent ceramic during the sintering process.

[0108] The fluorescent ceramic can be further cut, ground and polished to obtain the final fluorescent ceramic.

[0109] See also Figure 3 , Figure 3 Schematic diagram of the structure of the fluorescent ceramic comparative example. Figure 3 The composite fluorescent ceramic 2 shown is a composite fluorescent ceramic 2 in which no sintering aid is added during the sintering process, and no SiO2 layer is coated on the surface of the fluorescent powder particles. Under this condition, although the density of the composite fluorescent ceramic 2 sintered reaches about 96%, after the composite fluorescent ceramic 2 is cut, ground and polished, there are blocky aluminum oxide grains 22 peeled off at the edge of the fluorescent powder grains 21, forming holes 23. That is, although the density of the fluorescent ceramic can be improved by increasing the sintering temperature, the bonding force between the fluorescent powder grains 21 and the aluminum oxide grains 22 is poor, and the aluminum oxide grains 22 are easy to peel off during the mechanical processing. The peeling of the aluminum oxide grains 22 will have a great impact on the subsequent processing of the fluorescent ceramic, which is not conducive to other subsequent processing processes, such as packaging, coating, etc. In addition, the high temperature causes the edge of the fluorescent powder grain 21 to dissolve, so the edge of the fluorescent powder grain 21 is no longer smooth and pebble-like, and many pointed protrusions appear. The shape of the fluorescent powder grain 21 is seriously deformed and loses the best luminous shape, which will seriously affect the luminous performance of the fluorescent ceramic.

[0110] It is noted again that the above is only an implementation method of the present application and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A complex phase fluorescent ceramic, characterized in that: The complex phase fluorescent ceramic comprises aluminum oxide grains and phosphor grains; wherein the aluminum oxide grains have a particle size of 1-5 μm, and the phosphor grains have a particle size of 10-30 μm; the mass fraction of the phosphor grains in the complex phase fluorescent ceramic is 70% to 90%; and the relative density of the complex phase fluorescent ceramic is 99.0% to 99.9%.

2. The complex fluorescent ceramic according to claim 1, characterized in that: The complex phase fluorescent ceramic contains SiO2, and the SiO2 accounts for 0.05%-5% of the mass of the fluorescent powder grains.

3. The complex fluorescent ceramic according to claim 1, characterized in that: Among the phosphor crystal particles, at least 30% of the total phosphor crystal particles have a particle size of more than 15 μm.

4. The complex fluorescent ceramic according to claim 1, characterized in that: The relative density of the complex phase fluorescent ceramic is 99.5%-99.9%.

5. The complex fluorescent ceramic according to claim 1, characterized in that: The phosphor crystal particles have a smooth pebble shape.

6. A method for preparing a composite fluorescent ceramic, characterized in that: include: Prepare phosphor particles, wherein the particle size of the phosphor particles is 10-30 μm, and coat the surface of the phosphor particles with a SiO2 layer; Prepare alumina particles and a sintering aid, wherein the particle size of the alumina particles is 0.05 μm-1 μm; The phosphor particles coated with the SiO2 layer, the aluminum oxide particles and the sintering aid particles are mixed in proportion to obtain a raw material powder, wherein the weight ratio of the phosphor particles to the aluminum oxide particles is 7-9:1-3; Molding the raw material powder to obtain a green body; The green body is subjected to a first sintering step, wherein the first sintering step satisfies at least one of a sintering temperature of 1400° C. to 1600° C., a sintering time of 0.5 h to 3 h, and a sintering pressure of 30 to 100 MPa; The green body sintered in the first step is subjected to a second step of sintering, wherein the second step of sintering satisfies at least one of a sintering temperature of 1400° C. to 1700° C., a sintering time of 10 min to 100 min, and a sintering pressure of 100 to 200 MPa; The green body sintered in the second step is annealed to obtain the composite fluorescent ceramic.

7. The preparation method according to claim 6, characterized in that: The step of coating the surface of the phosphor particles with a SiO2 layer comprises: The phosphor particles, solvent and alkoxysilane are mixed, and the alkoxysilane is hydrolyzed to coat the surface of the phosphor particles with a SiO2 layer, wherein the mass of the SiO2 layer is 0.05%-5% of the mass of the phosphor particles.

8. The preparation method according to claim 6, characterized in that: The first sintering step is spark plasma sintering; the second sintering step is hot isostatic pressing sintering.

9. The preparation method according to claim 6, characterized in that: The sintering aids are magnesium oxide and yttrium oxide, and the mass of the sintering aids is 0.1% to 5% of the mass of the aluminum oxide particles.

10. A light emitting device, characterized in that: It comprises an excitation light source and the complex fluorescent ceramic as described in any one of claims 1 to 5.